Paralympic sprint performance between 1992 and 2012 - Grobler, L.; Ferreira, S.; Terblanche, E. (International Journal of Sports Physiology and Performance, 2015)
The Paralympic Games have undergone many changes since their inception in 1960, one being the advances made in running-specific prostheses (RSPs) for track athletes with lower-limb amputations. Purpose: To investigate the sprinting-performance changes in athletes with lower-limb amputations since 1992 to assess whether the influence of developments in RSP technology is evident. Methods: The results of the Olympic and Paralympic Games ranging between 1992 and 2012 for the 100-m and 200-m were collected, and performance trends, percentage change in performance, and competition density (CD) were calculated. Results: The results indicate that the greatest performance increases were seen in athletes with lower-limb amputations (T42 = 26%, T44 = 14%). These performance improvements were greater than for Olympic athletes (<3%), as well as Paralympic athletes from other selected classes (<10%). The T42 and T44 classes also showed the lowest CD values. Discussion: These results suggest that although there is an overall trend for improved Paralympic sprint performances, RSP technology has played a noteworthy role in the progression of performances of athletes with amputations. It is also hypothesized that the difference in the performance improvements between the T42 and T44 classes is due to the level of disability and therefore the extent to which technology is required to enable locomotion. Conclusion: It is evident that RSP technology has played a significant role in the progression of performances in athletes with lower-limb amputations